Clinicoepidemiological and laboratory profile of children with severe acute malnutrition admitted to a tertiary care centre - Bhat, Abdus Sami; Qureshi, Umer Amin; Nigeen, Waseeqa; Bashir, Iram; Khursheed, Shagufta (International Journal of Contemporary Pediatrics, 2020)
Background: Severe Acute Malnutrituon (SAM) is a form of malnutrition where there is an imminent threat of death to the child. The chances of complications are very high and in most case child requires hospitalization for stabilization and rehabiliatation. Objective of study the clinicoepidemiological and laboratory profile of children with severe acute malnutrition (SAM) admitted to a Nutritional Rehabilitation Centre (NRC) of our hospital. Methods: A retrospective chart review of admitted patients. Nutritional Rehabilitation centre (NRC) at GB Pant Hospital Government Medical College Srinagar over a one year period between June 2017 and June 2018. Results: Total of 187 patients of SAM was admitted in NRC during the study period. One hundred and eight (57.7%) were males and 79(42.3%) were females .Patients were equally among various districts. Infants (<12months) constituted the majority of admissions (54.5%). Marasmus was by far the commonest phenotype presenting as SAM (85.5%).Respiratory comorbidity was the commonest present in about 41 (26.3%) followed by daiarrhea in 32(20.5%). Delayed initiation of complimentary feeding was found in 75(40.1%) while early weaning was found in another 55 children (29.4%). Birth order more than three was present in 92 children (49%). Mother’s literacy status had a direct bearing on the prevalence of SAM. Most of the children were from rural background (75%).Most belonged to low economic and income class as around 65.2% had a very meager family income. Conclusions: SAM is more common in Infants and in children from rural background. It is highly associated with faulty feeding practices including lack of breast feeding and presence of mixed and faulty feeding. It is also associated with increasing birth order, low maternal education and low family income Pneumonia and diarrhea are leading comorbidities. Hypoglycemia and hypothermia are leading complications. Marasmus is the commonest phenotype.